2005
DOI: 10.1200/jco.2005.05.112
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Bevacizumab to Bolus Fluorouracil and Leucovorin in First-Line Metastatic Colorectal Cancer: Results of a Randomized Phase II Trial

Abstract: Addition of bevacizumab to FU/LV as first-line therapy in CRC patients who were not considered optimal candidates for first-line irinotecan treatment provided clinically significant patient benefit, including statistically significant improvement in progression-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
587
4
36

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 856 publications
(654 citation statements)
references
References 25 publications
27
587
4
36
Order By: Relevance
“…In patients on bevacizumab, hypertension had an overall incidence of up to 32% (Hurwitz et al, 2004;Kabbinavar et al, 2005); 11 -16% of patients required intensive therapy with multiple drugs (Grade 3), but only 1% had life-threatening hypertensive crisis (Grade 4). In patients on sunitinib, hypertension had an incidence of 28% (6% had Grade 3) in phase II trials in metastatic renal cell carcinoma (Motzer et al, 2006) and an incidence of 15% (4% had Grade 3) in a phase III trial in GIST (Demetri et al, 2005).…”
Section: (G -H)mentioning
confidence: 99%
See 2 more Smart Citations
“…In patients on bevacizumab, hypertension had an overall incidence of up to 32% (Hurwitz et al, 2004;Kabbinavar et al, 2005); 11 -16% of patients required intensive therapy with multiple drugs (Grade 3), but only 1% had life-threatening hypertensive crisis (Grade 4). In patients on sunitinib, hypertension had an incidence of 28% (6% had Grade 3) in phase II trials in metastatic renal cell carcinoma (Motzer et al, 2006) and an incidence of 15% (4% had Grade 3) in a phase III trial in GIST (Demetri et al, 2005).…”
Section: (G -H)mentioning
confidence: 99%
“…Proteinuria was found in 23% of 1132 patients in clinical trials of bevacizumab in various types of cancer and was more common in patients receiving bevacizumab plus chemotherapy than in patients on chemotherapy alone (Hurwitz et al, 2004;Kabbinavar et al, 2005). Proteinuria is typically asymptomatic and decreases after treatment ends.…”
Section: Proteinuriamentioning
confidence: 99%
See 1 more Smart Citation
“…The last stage is the maturation process, characterized by an increase in collagen content and tensile strength [15]. In phase II and III studies, the surgical wounds were exposed to bevacizumab therapy only during the maturation phase, that is, more than 28 days after surgery [4][5][6].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Preclinical studies have demonstrated deleterious effects of agent targeting vascular endothelial growth factor (VEGF) on the healing of ventral hernias and colonic anastomoses [1][2][3]. In fact, major surgery less than 28 days before the beginning of therapy has been an exclusion criterion in colorectal phase II and III studies with bevacizumab [4][5][6]. In the pivotal phase III trial in metastatic colorectal cancer, wound-healing complications occurred in 10 out of 75 (13%) bevacizumab-treated patients undergoing surgery compared to 1 out of 29 (3.4%) control patients.…”
Section: Introductionmentioning
confidence: 99%